ENTEROTOXIGENIC ESCHERICHIA COLI INTESTINAL PATHOGENESIS AND COLONIZATION RESISTANCE (Intent Research Scientific Journal, 2023)
This review discusses articles in the last 10 years about the etiology, pathogenesis, and clinical manifestations of ETEC, as well as gut microbiota-mediated resistance to colonization, its interactions in human small intestine, prevention strategies and most importantly modern diagnostic methods using cutting-edge technologies which provide new insights in reducing adverse human health impacts.